Saprochaete clavata invasive infection in a patient with severe aplastic anemia: Efficacy of voriconazole and liposomal amphotericin B with adjuvant granulocyte transfusions before neutrophil recovery following allogeneic bone marrow transplantation - Simon Favre (Medical Mycology Case Reports, 2016)
We report a case of a 27-year old man with severe aplastic anemia who developed a Saprochaete clavata (Geotrichum clavatum) disseminated invasive infection shortly prior a scheduled allogeneic bone marrow transplantation. Treatment with a combination of voriconazole, liposomal amphotericin B and adjuvant granulocyte transfusions was successful before neutrophil recovery.